Assessment of quality of life in Turkish children with psoriasis and their caregivers. Issue 5 (9th July 2018) - Tekin, Burak; Gurel, Mehmet Salih; Topkarci, Zeynep; Topaloglu Demir, Filiz; Aytekin, Sema; Cebeci Kahraman, Filiz; Singer, Ralfi; Erdemir, Vefa Asli; Uzuncakmak, Tugba Kevser; Yasar, Sirin; Akdeniz, Necmettin; Altunay, Ilknur Kivanc; et al.
Abstract: Background/Objectives: The effect of pediatric psoriasis on quality of life has been demonstrated, but data regarding its influence on caregiver quality of life are scarce. The objective was to investigate how psoriasis affects quality of life of children and their caregivers. Methods: This multicenter study included 129 children with psoriasis and their caregivers, who were family members accompanying patients to the clinic. Patient quality of life was measured using the Child Dermatology Life Quality Index. Caregiver quality of life was assessed using Dermatological Family Impact Scale, a 15‐item questionnaire validated for use in the Turkish language. Results: Mean Child Dermatology Life Quality Index score was 7.6, indicating a moderate effect on patient quality of life. Symptoms and feelings were the most severely impaired domains of patient quality of life, and emotions was the most severely impaired domain of caregiver quality of life. Dermatological Family Impact Scale score was significantly correlated with Child Dermatology Life Quality Index (correlation coefficient [ r ] = .554, P  <   .001) and Psoriasis Area and Severity Index ( r  =   .350, P  <   .001). Caregivers of patients receiving systemic agents or phototherapy had relative impairment of multiple domains of quality of life compared to caregivers of patients receiving topical treatment only. Conclusion: Psychosocial effect of pediatric psoriasis was shown to extend beyond the individual, highlighting the importance of addressing patient and caregiver quality of life concerns in an integrated approach.